(untitled) (The Review of Diabetic Studies, 2024)
Background Laboratory tests are important tools in primary care, but their use is sometimes inappropriate. Laboratory tests are essential for screening, diagnosis and monitoring of diseases and are extensively used both in primary care. There is ample evidence that many laboratory investigations requested are not necessary. Repeat laboratory investigations are a common cause of unnecessary requests. It is generally recognized that the number of laboratory tests are increasing far more than the number of patients. The increased uses of tests probably have benefited some patients through earlier diagnosis and treatment, however, their contribution to the quality of care also is debatable. This is especially the case when the usage is not based on clinical need and scientific evidence, but rather on habits, defensive medicine or similar causes. Aim of this systematic review was to reviews the better use to improve laboratory the literature for studies evaluating the effectiveness of use to improve primary care physician use of laboratory requesting in Makkah al-mokarramah city, Saudi Arabia in 2024. Methods: We systematically searched MEDLINE, EMBASE, Cochrane Central and SCOPUS databases to identify better use focused on reducing laboratory requesting patterns among primary care. The following study designs were considered: systematic reviews, randomized controlled trials, controlled before and after studies (CBAs). The population of interest was primary care physicians. Better uses were considered if they aimed to improve laboratory testing in primary care. Results: The searches produced studies after removing duplicates; high numbers of studies were excluded because the interventions were not applied to primary care. The search ended with 6 studies that met our pre-specified criteria and were included in the review. In total, 802 records of papers were identified from the search of the literature. Based on a title review, 494 records were excluded. Conclusion This review gives an overview of the strategies recently applied in primary care the improve laboratory requesting patterns among primary care physicians. The laboratory costs reported by some of the studies are supplementary information to the changes in number of tests and do not add further information to the analysis.